Fundamental of Entrepreneurship ENT300 : Ale Ale Sport Center / Hernyzawati Rani ... [et al.] - Rani, Hernyzawati; Nor Azlan, Nurul Shahrezan; Nor Azlan, Nurul Shahreeha; Mohd Zakaria, Zafirah (2014)
Business name of our company is Ale Ale Sport Center which located in Kota Samarahan. The busmess is in form partnership which consist four members. Each partners has contribute the same amount as initial capital which is RM 20 000 per partner except one partner that contribute RM 30 000 as initial own capital which is General Manager. All partners have give full attention to the business and entitled to participate in the business management. We agreed that Nurul Shahrezan Nor Azlan as General Manager of Ale Ale Sport Center, Nurul Shahreeha Nor Azlan as Marketing Manager, Zafirah Mohd Zakaria as Operational Manager and Hernyzawati Rani as Administration Manager. Because lack of manpower, we majority decided to responsible Nurul Shahrezan Nor Azlan carries two duties which is General Manager and representative of Financial Manager. The selection of the position is based on education, skills and experiences they had in previous hiring.